Mutualistic interactions between plants and birds on Kilimanjaro - Maximilian Vollstaedt; Matthias Schleuning; Katrin Böhning-Gaese (PANGAEA, 2018)
This dataset includes mutualistic interactions between flowering and fruiting plants and all bird and (few) mammal species feeding on these resources. The data was collected on an area of 30 x 100 m on all study plots except for Hel and FEr, where mutualistic interactions could not be observed. All interactions were recorded using direct observations with binoculars following a standardized sampling procedure. Interactions were observed during 25 h distributed over 5 days on each plot.
Supplement to: Vollstaedt, Maximilian; Ferger, Stefan W; Hemp, Andreas; Howell, Kim M; Böhning-Gaese, Katrin; Schleuning, Matthias (2018): Seed-dispersal networks respond differently to resource effects in open and forest habitats. Oikos, 127(6), 847-854, https://doi.org/10.1111/oik.04703